JOHN BELL ON THE CAMPAIGN OF PETER I TO DERBENT - Seferbekov, Magomedhabib Ruslanovic (History, Archeology and Ethnography of the Caucasus, 2022)
A number of publications have been devoted to the Persian campaign of Peter the Great and the stay of the Russian Imperial troops on the southwestern shores of the Caspian Sea in 1722–1735 – monographs, articles, dissertations, collections of documents and materials prepared with the use of a wide range of sources and literature. This topic continues to attract the attention of historians even today. It has acquired particular relevance in connection with the 350th anniversary of the birth of the first Russian Emperor Peter the Great and the 300th anniversary of the Persian campaign. A large number of documentary sources from the collections of the federal and regional archives of Russia cover the history of the Persian campaign and its results, which made it possible to reveal new episodes of imperial policy in the Caucasian-Caspian region in the first quarter of the 18th century. Among the most valuable sources on the history of the Persian campaign are the travel notes of the English-speaking authors – the direct participants and eyewitnesses of the events described. One of these sources is the John Bell’s book “Travels from St. Petersburg, across Russia, to different parts of Asia”, particularly, the section titled “Journey from Moscow to Derbent in Persia, in 1722”, translated by the author of the paper into Russian with commentaries. This translation may be a valuable contribution to both the ethnography and historiography of the Russian Caucasian studies of the first quarter of the 18th century.
Keywords: Persian campaign of 1722–1723; activity of Peter the Great; Caucasian-Caspian region; sources of English-speaking authors